STRESS MANAGEMENT (HOW TO TURN STRESS INTO HIGH PRODUCTIVITY) - Riza, Fahrul; Diayudha, Lanang; Wijaya, Andreas; Tannia, Tannia; Sudirga, Rudy Santosa (Jurnal Pengabdian dan Kewirausahaan, 2021)
ABSTRACT                 Stress Management (How To Turn Stress Into High Productivity). If you are living with high level of stress, you are putting your entire well-being at risk. It narrows your ability to think clearly, function effectively, and enjoy life. It may seem that there is nothing you can do about stress. Effective stress management help you break the hold stress has on your life, so you can be happier, healthier, and more productive. The ultimate goal is a balanced life, with time for work, relationships, rileksation and fun, and the resilience to hold up under pressure and meet challenges head on. Stress management starts with identifying the sources of stress in your life, this isn’t as straightforward as it sounds. While it’s easy to identify major stressors such as changing jobs, moving, or going through a divorce, pinpointing the sources of chronic stress can be more complicated. It’s all too easy to overlook how your own thoughts, feelings, and behaviors contribute to your everyday stress levels.A stress journal can help you identify the regular stressors in your life and the way you deal with them. Each time you feel stressed, keep track of it in your journal or use a stress tracker on your phone. The following stress management tips in this article can help you to overcome the stress in your life.